Investigation of the association between the genetic polymorphisms of the co-stimulatory system and systemic lupus erythematosus - Chen, Ding-Ping; Lin, Wei-Tzu; Yu, Kuang-Hui (Frontiers in Immunology, 2022)
Human leukocyte antigen genes have been shown to have the strongest association with autoimmune disease (AD). However, non-HLA genes would be risk factors of AD. Many genes encoding proteins that are related to T- and B-cell function have been identified as susceptibility genes of systemic lupus erythematosus (SLE). In this study, we explored the correlation between SLE and the genetic polymorphisms of co-stimulatory/co-inhibitory molecules, including CTLA4, CD28, ICOS, PDCD1, and TNFSF4. We found that there were nine single-nucleotide polymorphisms (SNPs) associated with SLE, namely, rs11571315 (TT vs. CT vs. CC: p < 0.001; TT vs. CT: p = 0.001; p = 0.005; TT vs. CT +CC: p < 0.001; TT+CT vs. CC: p = 0.032), rs733618 (CC vs. CT vs. TT: p = 0.002; CC vs. CT: p = 0.001; CC vs. TT: p = 0.018; CC vs. CT + TT: p = 0.001), rs4553808 (AA vs. AG: p < 0.001), rs62182595 (GG vs. AG vs. AA: p < 0.001; GG vs. AG: p < 0.001; GG vs. AG+AA: p < 0.001), rs16840252 (CC vs. CT vs. TT: p < 0.001; CC vs. CT: p < 0.001; CC vs. CT + TT: p < 0.001), rs5742909 (CC vs. CT: p = 0.027; CC vs. CT + TT: p = 0.044), rs11571319 (GG vs. AG vs. AA: p < 0.001, GG vs. AG: p < 0.001; GG vs. AG+AA: p < 0.001), rs36084323 (CC vs. CT vs. TT: p = 0.013, CC vs. TT: p = 0.004; CC vs. CT + TT: p = 0.015; CC +CT vs. TT: p = 0.015), and rs1234314 (CC vs. CG vs. GG: p = 0.005; CC vs. GG: p=0.004; CC+ CG vs. GG: p=0.001), but not in CD28 and ICOS by using the chi-square test. Additionally, rs62182595 and rs16840252 of CTLA and rs1234314 and rs45454293 of TNFSF4 were also associated with SLE in haplotypes. These SLE-related SNPs also had an association with several diseases. It was indicated that these SNPs may play an important role in immune regulation and pathogenic mechanisms.